Clinical outcome measures eight years following Coronary Artery Bypass Grafting (CABG): A prospective cohort study - Mackin, P; Skinner, J; Farrer, M; Albers, C; Neil, H; Adams, P (1999)
We prospectively studied over 8 years the outcome of 353 consecutive patients undergoing elective first time CABG surgery in a single centre in the North of England. At study entry mean age was 57.2 (sd 7.3) years, 84% were male, 98% had angina; 2% grade 1, 24% grade 2, 40% grade 3, 32% grade 4 (Canadian Cardiovascular Scale). At surgery patients had 2.75 (sd 0.77) graft conduits (75% LIMA, 13% RIMA) with 3.60 (sd 1.20) distal anastomoses. After 8 years survival status was known for all patients. 68 patients had died, cumulative survival 82%, 14 within 30 days of surgery, and 54 (30 cardiac) between 30 days and 8 years. 9 patients had further cardiac surgery (8 redo CABG, 1 transplant) and 6 had undergone PTCA. 267 (97%) patients without further cardiac surgery completed questionnaires (247 telephone, 10 postal, 10 clinic). 48 (18%) patients were under hospital outpatient follow up. 162 (61%) patients had angina; 26 (16%) grade 1, 65 (40%) grade 2, 34 (21%) grade 3 and, 18 (11%) grade 4. 41 (25%) patients with angina were taking no regular anti-anginal medication; 43 (27%), 46 (28%), 29 (18%) and 3 (2%) were taking 1, 2, 3 or 4 anti-anginal agents respectively. 233 (87%) patients took aspirin. Ninety-six (37%) patients were taking lipid-lowering drugs. 34 (44%) and 5 (50%) patients with total cholesterol 6.5 mmol l-1 and 7.8 mmol l-1 at five years respectively were not taking lipid lowering drugs. Conclusions: Mortality is low 8 years following CABG surgery, and over 40% of patients remain free from angina. Angina and hyperlipidaemia is under-treated in these high-risk patients and more patients should be under follow up by a hospital cardiologist.